2022
DOI: 10.1038/s41567-022-01827-1
|View full text |Cite|
|
Sign up to set email alerts
|

Quantum coherence tomography of light-controlled superconductivity

Abstract: The coupling between superconductors and oscillation cycles of light pulses, i.e., lightwave engineering, is an emerging control concept for superconducting quantum electronics. Although progress has been made towards terahertz-driven superconductivity and supercurrents, the interactions able to drive non-equilibrium pairing are still poorly understood, partially due to the lack of measurements of high-order correlation functions. In particular, the sensing of exotic collective modes that would uniquely charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 51 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Differentiating between the Higgs and Cooper pair breaking contributions to THG signals is a challenging task. Recent studies have suggested that 2D terahertz spectroscopy, which involves varying both gating time and pump-probe delay time, is an efficient way for distinguishing between the two pathways (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Differentiating between the Higgs and Cooper pair breaking contributions to THG signals is a challenging task. Recent studies have suggested that 2D terahertz spectroscopy, which involves varying both gating time and pump-probe delay time, is an efficient way for distinguishing between the two pathways (39,40).…”
Section: Resultsmentioning
confidence: 99%
“…The direct comparison with TR-ARPES data ( 47 ), where similar suppression and recovering dynamics have been reported, provides a benchmark of the ability of 2D THG spectroscopy to directly access the pump-induced quench of the SC order. On a similar avenue, 2D THz experiments with broadband pulses ( 48 , 49 ) could serve as probes for the transient regime. 2D transient THG spectroscopy thus offers an additional tool to investigate the quenching and recovery of the Higgs and phase excitations of the SC condensate in unconventional superconductors and sheds light on the fundamental pairing mechanism at play in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum coherence is another key quantum resource that makes clear the boundary between the quantum and classical contexts. Some extensive quantum phenomena such as interference [25], laser [26], superconductivity [27] and superfluidity [28,29] may be interpreted based on quantum coherence. In fact, quantum coherence provides some profound merits for quantum metrology [30,31], quantum key distribution [32], entanglement creation [33,34].…”
Section: Introductionmentioning
confidence: 99%